Legality of Virtual Hindu Marriage in the Perspective of National Law in Indonesia - Arthadana, Made Gede; Wibawa, I Putu Sastra; Sarjana, I Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024)DO - 10.24843/JMHU.2024.v13.i04.p09, 2024)
The general purpose of writing in this scientific journal is to find out the legal basis for marriage for Hindus in Bali and specifically to find out the legality of virtual Hindu marriages from the perspective of National Law in Indonesia. The writing method used is descriptive normative legal research using a statutory approach and a case approach. The first research result is the Legal Basis for Hindu Marriage in Bali, which refers to Article 28 paragraph (1) of the 1945 Constitution, Article 1 & Article 2 of Law Number 1 of 1974 concerning Marriage, Law Number 16 of 2019 concerning Amendments Based on Law Number 1 of 1974 concerning Marriage, Rigveda X. 85.23 & Rigveda VI.15.19. The second research result, namely the Legality of Virtual Hindu Marriages in the Perspective of Law Number 1 of 1974 concerning Marriage, is that national norms do not regulate virtual marriages so it can be said to be an empty norm. Viewed from custom, tradition and religion, there are no rules regarding virtual marriage because it can be seen that the conditions that must be met to make a Hindu marriage in Bali valid are one of the witnesses in the mabyakala (wiwaha) ceremony which involves 3 witnesses or Tri Upasaksi, namely the witness god, human witnesses, and bhuta witnesses.